(untitled) (Dissertare, 2017)
The purpose of this paper is to present an advance of research on the epistemological level, on the concepts "hybridity, culture and identity", from the reflection that such terms have been studied by different authors, without being able to consolidate them to define the Latin American reality. This contribution presents some initial considerations that arise from the confrontation of the ideas of the authors on the meaning of hybrid thinking, with particular reference to art and painting. From the methodological point of view, the work uses an interpretative-comparative approach and analysis and exegesis techniques to review the thinking of authors such as: García Canclini (1990), Bhabha (1994), Del Toro (2002), Cornejo Polar (2002) ), Chacón (2004) and Giddens (2002), among others. From the epistemological discussion it can be concluded that: a) from a process of interpretation and exegesis there are significant and symbolic indications of what among these lines will be called "hybrid thinking", typical of Latin American culture; b) research in hydrology allows us to explore and propose new perspectives to broaden the discussion around the issue and consolidate a theoretical-ideological set that allows us to understand what our Latin American identity is; c) finally, the terms "hybridity, culture and identity" are immersed in a reality that has transited, from the past to the present, by influences of hybrid thinking, which has not been fully accepted, but which continues to influence socio-cultural actions.